Evaluation of VITEK 2 Compact and VITEK MS in the identification of coagulase-negative staphylococci isolated from blood cultures - Silva,Camila Gabriela da (2017)
ABSTRACT Introduction: In most clinical laboratories, coagulase-negative staphylococci (CNS) are classified through their biochemical characteristics using traditional and/or automated phenotypic methods. However, identification by phenotypic method is a great challenge despite the improvement in identification by automated systems in recent years. Objective: The main objective was to compare the identification of CNS between two automated methods: phenotypic (VITEK® 2 Compact, bioMérieux) and mass spectrometry (MALDI-TOF VITEK® MS, bioMérieux). Materials and method: 133 CNS isolates from whole blood samples from September 2015 to May 2016 were analyzed. Results: All the 133 isolates were identified by VITEK® 2 Compact as CNS, whereas VITEK MS did not identify seven, and there was uncertainty among three species in one isolate. The two devices had a concordance of 92.8% (117/126) of which: 56 Staphylococcus epidermidis, 34 Staphylococcus hominis ssp. hominis, 15 Staphylococcus haemolyticus, 10 Staphylococcus capitis, one Staphylococcus cohnii ssp. urealyticus and one Staphylococcus sciuri. There was disagreement in identification of S. lugdunensis and S. aureus. Conclusion: Through the analysis between the two devices and based on scientific articles comparing the methods involved in the study, it was possible to observe the great biochemical similarity among the coagulase-negative staphylococci species, this being the main limitation of the phenotypic method. The VITEK MS equipment showed high discrimination between species when compared to the gold standard method, besides being rapid and easy to use.